ENVIRONMENTAL DNA IN AN OCEAN OF CHANGE: STATUS, CHALLENGES AND PROSPECTS: DNA ambiental em um oceano de mudanças: status, desafios e perspectivas - Havermans, Charlotte; Dischereit, Annkathrin; Pantiukhin, Dmitrii; Friedrich, Madlen; Murray, Ayla (Arquivos de Ciências do Mar, 2022)
Environmental DNA (eDNA) studies have burgeoned over the last two decades and the application of eDNA has increased exponentially since 2010, albeit at a slower pace in the marine system. We provide a literature overview on marine metazoan eDNA studies and assess recent achievements in answering questions related to species distributions, biodiversity and biomass. We investigate which are the better studied taxonomic groups, geographic regions and the genetic markers used. We evaluate the use of eDNA for addressing ecological and environmental issues through food web, ecotoxicological, surveillance and management studies. Based on this state of the art, we highlight exciting prospects of eDNA for marine time series, population genetic studies, the use of natural sampler DNA, and eDNA data for building trophic networks and ecosystem models. We discuss the current limitations, in terms of marker choice and incompleteness of reference databases. We also present recent advances using experiments and modeling to better understand persistence, decay and dispersal of eDNA in coastal and oceanic systems. Finally, we explore promising avenues for marine eDNA research, including autonomous or passive eDNA sampling, as well as the combined applications of eDNA with different surveillance methods and further molecular advances. Keywords: environmental DNA, DNA metabarcoding, marine metazoa, biodiversity, population genetics, natural sampler DNA, diet analysis.